Maternal factors influencing complete basic immunization: A Scoping Review - Hatijar; Risna Ayu Rahmadani; Asridawati Akib; Jennifer A Barr (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Immunization is one of the most effective public health interventions to prevent infectious diseases in children. However, achieving complete basic immunization coverage remains a global challenge, particularly in low- and middle-income countries. Maternal factors play a crucial role in determining whether children receive complete immunization. Understanding these factors is essential to inform strategies for improving immunization coverage. Methods: This scoping review followed the PRISMA-ScR framework to map existing evidence on maternal determinants of complete basic immunization. A systematic search was conducted in electronic databases such as PubMed, Scopus, and Google Scholar, covering publications between 2010 and 2025. Inclusion criteria were peer-reviewed studies addressing maternal characteristics related to childhood immunization completion. Data were extracted and categorized thematically. Results: The reviewed studies revealed several maternal factors influencing complete immunization. These included maternal education, knowledge and awareness of immunization benefits, socioeconomic status, access to health facilities, and household decision-making autonomy. Maternal age, parity, and antenatal care attendance also showed significant associations with immunization completion. The identified barriers included limited health literacy, cultural beliefs, and logistical challenges such as distance to health services. Conclusion: Maternal factors are central determinants in achieving complete basic immunization. Strategies to increase coverage should prioritize maternal education, empowerment, and accessibility to health services. Strengthening maternal involvement in child health programs can significantly improve immunization rates and reduce preventable childhood morbidity and mortality.